Copper Acetoacetonate [Cu(acac)2]/BINAP‐Promoted Csp3N Bond Formation via Reductive Coupling of N‐Tosylhydrazones with Anilines. Issue 11 (9th August 2013) - Aziz, Jessy; Brion, Jean‐Daniel; Hamze, Abdallah; Alami, Mouad
Abstract We report the the copper(II) acetoacetonate [Cu(acac)2]/BINAP‐catalyzed synthesis of arylamines from N‐tosylhydrazones and anilines. A fine tuning of the reaction conditions was required to accomplish the cross‐coupling successfully, including the ligands effect and the addition of small amounts of water. The characteristic feature of this protocol is its functional group compatibility and its chemoselectivity when various aminophenol derivatives were used. Taking into consideration the interest for this copper‐reductive coupling in which no stoichiometric metal hydride reagent is employed, this can be considered as an alternative to the conventional reductive amination. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>